2013
DOI: 10.3389/fpsyg.2013.00991
|View full text |Cite
|
Sign up to set email alerts
|

Now you see it, now you don't: on emotion, context, and the algorithmic prediction of human imageability judgments

Abstract: Many studies have shown that behavioral measures are affected by manipulating the imageability of words. Though imageability is usually measured by human judgment, little is known about what factors underlie those judgments. We demonstrate that imageability judgments can be largely or entirely accounted for by two computable measures that have previously been associated with imageability, the size and density of a word's context and the emotional associations of the word. We outline an algorithmic method for p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 79 publications
3
60
0
Order By: Relevance
“…Our results suggest that further understanding of the construct of arousal may be made by interpreting its relationship to concreteness. Westbury et al (2013) demonstrated that affective measures can account for a large portion of the psychologically relevant variation contained within human judgments of imageability. Computer-estimated imageability judgments (from Westbury et al, 2013), in turn, are closely related to Brysbaert, Warriner, and Kuperman's (2014) concreteness judgments (r = .77 over 5,278 words).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our results suggest that further understanding of the construct of arousal may be made by interpreting its relationship to concreteness. Westbury et al (2013) demonstrated that affective measures can account for a large portion of the psychologically relevant variation contained within human judgments of imageability. Computer-estimated imageability judgments (from Westbury et al, 2013), in turn, are closely related to Brysbaert, Warriner, and Kuperman's (2014) concreteness judgments (r = .77 over 5,278 words).…”
Section: Discussionmentioning
confidence: 99%
“…Westbury et al (2013) demonstrated that affective measures can account for a large portion of the psychologically relevant variation contained within human judgments of imageability. Computer-estimated imageability judgments (from Westbury et al, 2013), in turn, are closely related to Brysbaert, Warriner, and Kuperman's (2014) concreteness judgments (r = .77 over 5,278 words). The explanation we propose for why judgments of concreteness are so strongly related to PC2 is that, like imageability judgments, concreteness judgments are affective in nature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, however, that the radical and highly reliable difference in predictive power between the imageability-specific affect model developed in Westbury et al (2013) (r = .57 for the same 2532 words) and the two valence measures suggests that it is not valence per se that is predictive of imageability, but rather that valence is correlated with a different measure of affective force that is itself very highly predictive of imageability.…”
Section: Assessing Validitymentioning
confidence: 96%
“…Concreteness coding was done by word type and concreteness ratings were calculated using a database of 3814 words that had been assigned imageability judgments (database complied by Westbury et al, 2013). The average percentage of word types for which concreteness ratings were available in the screen condition was 68.0% (SD = 2.9%) and in the screen-down condition 69.5% (SD = 3.0%), a difference that was significant on a repeated measures ANOVA, F (1, 31) = 6.15, p = .019, eta squared = .166.…”
Section: Codingmentioning
confidence: 99%